IL-17 and related cytokines involved in systemic sclerosis: Perspectives - Rafaela Silva Guimarães Gonçalves; Michelly C. Pereira; Andréa Tavares Dantas; Anderson Rodrigues de Almeida; Claudia Diniz Lopes Marques; Moacyr J. B. M. Rego; Ivan R. Pitta; Angela Luzia Branco Pinto Duarte; Maira Galdino R. Pitta (Autoimmunity, 2018)
Systemic sclerosis (SSc) is a multisystemic, complex, and rare disease of connective tissue, with high morbidity and mortality, and without specific treatment. The disease is characterized by three main principles: vascular disease, autoantibody production and inflammation, and fibrosis. Since it is well defined that SSc is characterized by elevated production of TGF-β, IL-6, and IL-1, all of them cytokines related to Th17 differentiation, the hypothesis is that this disease may be strongly related to a polarization of the immune response towards the Th17 pathway. Considering the importance of a better understanding of the pathophysiology of Th17 pathway in SSc, this article aims to propose an update for a better understanding of current knowledge on main cytokines secreted by the Th17 cells (IL-17 A, IL-21, and IL-22) and the future prospects in the current disease.